Analisis Pengaruh Keikutsertaan Dalam Organisasi REMO Terhadap Perkembangan Karakter Sosial Pada Mahasiswa - Nirwasita, Paramesti; Nurharini, Atip; Arlani, Krisma Arisma Dwi; Khoirunnisa, Nadia; Firdaus, Sectio (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
REMO or the abbreviation for Rebana Modern is an organization at UNNES which operates in the field of Islamic art. Activities in the REMO organization can improve character development in students at UNNES PGSD, especially in social character values. Through routine activities, the character that is formed includes discipline, self-confidence, mutual respect, spiritual values, togetherness, and Islamic artistic values. The many characters that are formed through REMO activities are something that has positive value. The focus of the character that we study through REMO activities is social character. This research uses a qualitative approach. Qualitative research is research that uses events, analysis of phenomena, social activities, thoughts of a person or a group. Qualitative research produces data in the form of written or verbal descriptions of the results of face-to-face and virtual interviews.